Redefining the Air Defence Identification Zone in the Framework of Customary International Law - Hadisusilo, Priyo; Riyanto, Sigit; Purwanto, Harry (Yustisia, 2022)
The use of force against other countries is strictly prohibited and has the character of jus cogens. However, this provision is not rigidly applied in the self-defence context codified in the United Nations Charter 1945 Article 51, also in the air defence context through the existence of the Air Defence Identification Zone (ADIZ). This research discusses whether ADIZ embodies the anticipatory efforts in the framework of customary international law. The research results indicate that the determination of ADIZ is not a form of self-defence principle in Article 51, which is the realm of jus ad bellum. Moreover, the conservative self-defence prerequisites in Article 51 are no longer relevant in line with the revolutionary development of aviation and its armament technology. Therefore, ADIZ as a state security practice constitutes a form of anticipatory efforts within the framework of long-standing state practice as customary international law.